Socialist Ensembles : Theater and State in Cuba and Nicaragua. - Martin, Randy (Cultural politics., 1994)
An ethnography of theater and political culture in Cuba and Nicaragua, Martins work reveals the tensions and negotiations among different dimensions of society that characterize the socialist project. Martin considers Nicaragua from the Sandinista through the Chamorro administrations, and Cuba from the time of the reforms known as rectification through the withdrawal of Soviet aid.